2021
DOI: 10.1111/ans.16763
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 3D printed abdominal aortic aneurysm phantoms: a systematic review

Abstract: Background: 3D printed (3DP) abdominal aortic aneurysm (AAA) phantoms are emerging in the literature as an adjunct for the visualization of complex anatomy, particularly for presurgical device selection and simulation. This is the first systematic review to provide a comprehensive overview of 3DP for endovascular aneurysm repair (EVAR) planning and intervention, evaluating the readiness of current levels of technology for mainstream implementation. Methods: A systematic literature search of PubMed and MEDLINE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Studies have confirmed that women with AAA have a higher risk of rupture than men, and smokers and those with untreated hypertension are also at increased risk (25)(26)(27). It is still a hot research topic to assess the specific rupture risk of patients with AAA by monitoring aneurysm volume, aortic size index (ratio of body surface area to aneurysm diameter), family history of (29,30) have shown that MMP-2 and MMP-9 are interdependent and synergistic in the progression of AAA. In addition to MMP-2 and MMP-9, whether other MMPs are involved in the pathogenesis of aneurysms should be further studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have confirmed that women with AAA have a higher risk of rupture than men, and smokers and those with untreated hypertension are also at increased risk (25)(26)(27). It is still a hot research topic to assess the specific rupture risk of patients with AAA by monitoring aneurysm volume, aortic size index (ratio of body surface area to aneurysm diameter), family history of (29,30) have shown that MMP-2 and MMP-9 are interdependent and synergistic in the progression of AAA. In addition to MMP-2 and MMP-9, whether other MMPs are involved in the pathogenesis of aneurysms should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Further, MMP-2 can also shear elastin and type IV collagen. Studies ( 29 , 30 ) have shown that MMP-2 and MMP-9 are interdependent and synergistic in the progression of AAA. In addition to MMP-2 and MMP-9, whether other MMPs are involved in the pathogenesis of aneurysms should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Yang and colleagues [87] mentioned the following pediatric surgical sub-specialties: neurosurgery, cardiothoracic Surgery, plastic Surgery, cardiovascular surgery, urological surgery, orthopedics, ENT surgery, oncological surgery and vascular surgery. Further medical fields include plastic surgery [93,94], traumatology [95][96][97], urology [98][99][100][101][102] and vascular surgery [103][104][105][106]. The affected organs or organ systems include the aorta [13,103,106], bladder [29], brain [35,37,39], cranium [30, 31, 34, 36, 44, 48-50, 53-55, 82, 84, 86, 91], ear [48, 78-81, 83, 93], female internal genitals [46], heart [2-12, 87, 88, 104], jaw [17, 20, 21, 23, 25, 47-52, 55, 56], kidney [29,41,98,[100][101][102], lip [94], liver [19,22,28], musculoskeletal system [20, 21, 24, 31-33, 38, 43, 57-77, 89, 90, 92, 93, 95-97], prostate [98,99], rectum and colon [14,40,42,45], spine…”
Section: Non-invasive Applicationsmentioning
confidence: 99%
“…Yang and colleagues [87] mentioned the following pediatric surgical sub-specialties: neurosurgery, cardiothoracic Surgery, plastic Surgery, cardiovascular surgery, urological surgery, orthopedics, ENT surgery, oncological surgery and vascular surgery. Further medical fields include plastic surgery [93, 94], traumatology [9597], urology [98102] and vascular surgery [103106].…”
Section: Reviews In Medical 3d Printingmentioning
confidence: 99%
“…As the technology has entered the mainstream consciousness, Urologists have capitalised on its strengths to 3D print anatomical models within the hospital environment [ 2 , 3 ]. The technology allows for the creation of patient-specific models for visual and tactile interrogation, positioning it as a natural adjunct for complex cases where adequate visualisation of each patient’s unique anatomy is paramount [ 4 ].…”
Section: Introductionmentioning
confidence: 99%